2017
DOI: 10.1016/j.celrep.2017.10.101
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Cerebellar Purkinje Cell Population Activity during Postnatal Refinement of Climbing Fiber Network

Abstract: Neural circuits undergo massive refinements during postnatal development. In the developing cerebellum, the climbing fiber (CF) to Purkinje cell (PC) network is drastically reshaped by eliminating early-formed redundant CF to PC synapses. To investigate the impact of CF network refinement on PC population activity during postnatal development, we monitored spontaneous CF responses in neighboring PCs and the activity of populations of nearby CF terminals using in vivo two-photon calcium imaging. Population acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In regard to the molecules that mediate activities of PCs, previous studies have shown that the P/Q-type voltage-dependent Ca 2+ channel (VDCC), the major VDCC in PCs, is essential for all four phases of CF synapse remodeling during postnatal cerebellar development 17, 22, 23 ( Figure 2). In addition, a study using in vivo whole-cell recording from single PCs 24 and a recent report of two-photon calcium imaging of PC population activities 25 strongly support that P/Q-VDCC is crucial for strengthening of single “winner” CF inputs ( Figure 2). On the other hand, the late phase of CF elimination has been shown to require the metabotropic glutamate receptor subtype 1 (mGluR1)–to–protein kinase Cγ (PKCγ) cascade in PCs 2631 , involves activation of the immediate early gene Arc 22, 32 , and is regulated by GABAergic inhibition of the PC soma by basket cells 33 ( Figure 2).…”
Section: Multiple Phases Of Developmental Cf-to-pc Synapse Remodelingmentioning
confidence: 62%
“…In regard to the molecules that mediate activities of PCs, previous studies have shown that the P/Q-type voltage-dependent Ca 2+ channel (VDCC), the major VDCC in PCs, is essential for all four phases of CF synapse remodeling during postnatal cerebellar development 17, 22, 23 ( Figure 2). In addition, a study using in vivo whole-cell recording from single PCs 24 and a recent report of two-photon calcium imaging of PC population activities 25 strongly support that P/Q-VDCC is crucial for strengthening of single “winner” CF inputs ( Figure 2). On the other hand, the late phase of CF elimination has been shown to require the metabotropic glutamate receptor subtype 1 (mGluR1)–to–protein kinase Cγ (PKCγ) cascade in PCs 2631 , involves activation of the immediate early gene Arc 22, 32 , and is regulated by GABAergic inhibition of the PC soma by basket cells 33 ( Figure 2).…”
Section: Multiple Phases Of Developmental Cf-to-pc Synapse Remodelingmentioning
confidence: 62%
“…We note, however, that additional mechanisms could work in parallel to effectively control the dimensionality, such as pruning of irrelevant inputs [80]. In the olivo-cerebellar system, in particular, climbing fiber-Purkinje-cell synapses are gradually eliminated based on IO activity during development [81,82]. We further note that our proposal of dimension reduction of an oscillatory system via coupling-induced synchronization contrasts other neural networks (e.g., auto-encoders) in that we propose a framework of neural communication among neurons for transmitting information rather than approximating a function that maps the data from high-dimensional space to low-dimensional space (i.e, encoding/decoding).…”
Section: Synchrony As a Mechanism For Controlling Dimensionalitymentioning
confidence: 99%
“…A second possibility is that the differentiation of iPCs is dictated by the timing of the establishment of the cerebellar circuitry. We speculate that efficient regeneration is possible at P1 because PCs still have an immature morphology and integration into the cerebellar circuitry, whereas at later stages the parallel fibers (axons of granule cells) synapse with PCs and climbing fibers (axons of the inferior olive neurons) refine their synapses and both cells promote PC maturation ( Good et al, 2017 ; Hoxha et al, 2017 ). Thus, maturation and integration of a newly generated PC into the cerebellar circuitry might not be efficient or possible after P5.…”
Section: Resultsmentioning
confidence: 99%